The effect of the mind on the clarity of the significance of the linguistic discourse of Judge Abd al-Jabbar al-Mu'tazili (Journal of the College of Basic Education, 2023)
The mind is considered the foundation, or the main pillar upon which the Mu'tazilites in general, and Judge Abd al-Jabbar al-Mu'tazili in particular, relies on, because of the clear importance of the mind in removing ambiguity from linguistic texts, interpreting the allegorical and referring it to the arbitrator, and knowing the evidences of justice and unification, truth and metaphor, as they are Subject to the mind and its significance, and I will try in this research to know the impact of the mind in those axes, and I ask God Almighty to make this research purely for the sake of the generous.The Mu'tazilites cared about the mind and their enemy's basic cognitive evidence, and used it in controversy and discussion, and emphasized the precedence of the rational side over the auditory side, and its dominance. Judge Abd al-Jabbar al-Mu'tazili (d.